Vibrant Matter A Political Ecology of Things - Bennett, Jane, 1957- (Book collections on Project MUSE., 2010)
Theorizes the political agency of things and natural phenomena-such as trash, food, weather, and electricity-to examine how non-human elements exert force on human politics and social relations.